2004
DOI: 10.1128/jvi.78.22.12395-12405.2004
|View full text |Cite
|
Sign up to set email alerts
|

Perforin and Fas Act Together in the Induction of Apoptosis, and Both Are Critical in the Clearance of Lymphocytic Choriomeningitis Virus Infection

Abstract: In this report we questioned the current view that the two principal cytotoxic pathways, the exocytosis and the Fas ligand (FasL)/Fas-mediated pathway, have largely nonoverlapping biological roles. For this purpose we have analyzed the response of mice that lack Fas as well as granzyme A (gzmA) and gzmB (FasxgzmAxB ؊/؊ ) to infection with lymphocytic choriomeningitis virus (LCMV). We show that FasxgzmAxB ؊/؊ mice, in contrast to B6, Fas ؊/؊ , and gzmAxB ؊/؊ mice, do not recover from a primary infection with LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 67 publications
3
24
0
Order By: Relevance
“…In contrast, when there is a massive virus infection that has infected large numbers of cells, it might be advantageous for the CTL to kill all surrounding cells, sacrificing some noninfected cells to quickly clear the virus. Indeed, recent studies have suggested that FasL may be important for clearing chronic infections (7,8). It would be of interest to investigate the contribution from particular FasL pools (stored versus de novo synthesized) for the antiviral immunity during these infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, when there is a massive virus infection that has infected large numbers of cells, it might be advantageous for the CTL to kill all surrounding cells, sacrificing some noninfected cells to quickly clear the virus. Indeed, recent studies have suggested that FasL may be important for clearing chronic infections (7,8). It would be of interest to investigate the contribution from particular FasL pools (stored versus de novo synthesized) for the antiviral immunity during these infections.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies suggested that FasL was largely dispensable for viral clearance in the relatively few systems that were examined (6). However, more recent studies suggest that FasL may be important for clearing persistent infections (7,8) and may contribute, along with the perforin pathway, to the shaping of the diversity of escape variants of influenza (9). Although FasL is not required for clearance of viruses that induce hepatitis in mice, it appears to contribute to viral pathogenesis because of significant bystander killing of hepatic cells (10)(11)(12).…”
mentioning
confidence: 99%
“…Aliquots of liver tissues were homogenized and used for determination of virus titers as described elsewhere. 39 Generation of ex vivo CD8 þ cells. On day 8 p.i., CD8 þ cells were positively selected from the spleen using a-CD8-MicroBeads (Miltenyi Biotec, Bergisch Gladbach, Germany) with an autoMACS (Miltenyi Biotec) and resuspended in MEM/5% FCS before use in cytotoxic assays as described previously.…”
Section: Discussionmentioning
confidence: 99%
“…of LCMV-WE according to established protocols. 25,39 IL-1Ra (Anakinra) treatment. Mice were injected 1 day before infection with 10 5 p.f.u.…”
Section: Discussionmentioning
confidence: 99%
“…Splenocytes, mouse granulocytes, and human PBMCs and PMNs were washed with FACS-washing buffer (PBS, 5% FCS, 0.1% NaN 3 ) as previously described 31 and incubated with 10 L mAbs for 20 minutes. ␣Mouse (m) mAb used were fluorescein isothiocyanate (FITC)-and phycoerythrin (PE)-labeled ␣B220 (clone RA3-6B2), PE-labeled ␣CD8 (clone 53-6.7), FITC-and PE-labeled ␣Gr-1 (clone RB6-8C5), FITC-labeled ␣Mac-1 (clone M1/70), FITC-and PE-labeled ␣NK1.1 (clone PK136), and FITC-and PE-labeled ␣Thy1.2 (clone 53-2.1).…”
Section: Flow Cytometrymentioning
confidence: 99%